2001
DOI: 10.1007/bf02373562
|View full text |Cite
|
Sign up to set email alerts
|

Quantum chemical modelling case studies relevant to metal oxide dissolution and catalysis

Abstract: Abstract. Over the past 20 years quantum-chemical methods have been developed sufficiently so that they can now be applied to the elucidation of the complex mechanistic processes that occur during metal oxide dissolution and catalysis reactions. Many of the reactions occurring during these processes are not directly accessible to experimental techniques and therefore quantum-chemical modelling can be applied to probe the individual reaction steps involved in the overall mechanism.Quantum chemistry provides the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 110 publications
2
9
0
Order By: Relevance
“…The absolute value of this MSINDO deviation is similar to that of the B3LYP method for this system, Ϫ115 kJ/mol, as obtained from periodic calculations. 55 Similar trends can be found in the systems anatase and vanadium pentoxide. For anatase four tetragonal clusters have been chosen, 2ϫ2ϫ1, 2ϫ2ϫ2, 4ϫ4ϫ1, and 6ϫ6ϫ1 ͓translation unit shown in Fig.…”
Section: A Binding Energysupporting
confidence: 70%
“…The absolute value of this MSINDO deviation is similar to that of the B3LYP method for this system, Ϫ115 kJ/mol, as obtained from periodic calculations. 55 Similar trends can be found in the systems anatase and vanadium pentoxide. For anatase four tetragonal clusters have been chosen, 2ϫ2ϫ1, 2ϫ2ϫ2, 4ϫ4ϫ1, and 6ϫ6ϫ1 ͓translation unit shown in Fig.…”
Section: A Binding Energysupporting
confidence: 70%
“…2 depicts the calculated binding energy per TiO 2 unit, as a function of the relative average coordination number, K. The extrapolated bulk value (K = 1) of 2000 kJ/mol obtained is 105 kJ/ mol higher than the value of 1895 kJ/mol for the heat of atomization DH a (approximated as E Bu ) obtained from experimental data [22,28]. The absolute value of this MSINDO deviation is similar to that of the DFT B3LYP method for this system, À115 kJ/mol, as obtained from periodic boundary calculations [29]. Furthermore, recent MSINDO calculations with the cyclic cluster model gave an extrapolated E Bu value of 2014 kJ/mol [30], which is slightly larger than the present value.…”
Section: Cluster Modelssupporting
confidence: 52%
“…[12] The electron correlation is described with the Perdew-Wang correlation functional. [12] In previous studies of MgO, NiO, CoO, and TiO 2 [11,13] it was found that the PW1PW method describes structural, energetic and electronic properties of crystalline materials with higher accuracy than other DFT methods.…”
Section: Methodsmentioning
confidence: 98%